Advancing Football Analytics: Predictive Modeling and Performance Analysis in the Bundesliga Using Machine Learning - Edalatpanah, Seyyed Ahmad; Hess, Markus (Computational Engineering and Technology Innovations, 2024)
The Bundesliga Data Shootout (BDS) is an innovative competition that merges the thrill of professional football with the analytical power of Data Science (DS). Its primary aim is to foster collaboration between data scientists and football enthusiasts to explore and harness the vast data available from Germany's premier football league, the Bundesliga. The competition encourages participants to develop creative, data-driven models to uncover new insights, enhance Performance Analysis (PA), and refine Decision-Making (DM) processes within the sport. By leveraging extensive datasets that include player statistics, match outcomes, and team performance metrics, the competition empowers participants to apply cutting-edge Machine Learning (ML) techniques, fostering advancements in Football Analytics (FA). This initiative not only enhances our understanding of the game but also demonstrates the transformative role that DS can play in shaping the future of football strategy and performance evaluation.